Noise Affects Multimodal Communication During Courtship in a Marine Fish - de Jong, Karen; Amorim, M. Clara P.; Fonseca, Paulo J.; Heubel, Katja U. (Frontiers in Ecology and Evolution, 2018)
Selection pressures on signals can be substantially modified by a changing environment, but we know little about how modified selection pressures act on multimodal signals. The currently increasing levels of anthropogenic noise in the ocean may affect the use of acoustic signaling relative to other modalities. In the Painted Goby (Pomatoschistus pictus), visual and acoustic signals are associated during courtship behavior, but females usually rely more heavily on acoustic signals than on visual signals in mate choice. In an aquarium experiment, we compared male courtship behavior and female spawning decisions between silent treatments and treatments with additional noise. We found that the relationships between male characteristics, male visual and acoustic courtship, and spawning success were affected by noise. A path analysis revealed that females pay more attention to visual courtship in noisy circumstances compared to control. We conclude that environmental stressors can cause shifts in the use of different signaling modalities for spawning decisions and discuss how selection pressures on multimodal signals may change with increasing noise-levels.